Pengujian Model Hujan - Aliran Pada Musim Yang Berbeda Untuk Daerah Aliran Sungai Kecil =Testing Storm Rainfall - Runoff Model in Different Season for Small Watershed - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstrak Hamon had developed a model, based on the water balance approach, to estimate direct runoff small watersheds having five parameters namely: a and b were constant that depend upon watershed characteristics, c was constant that depended upon retained rainfall, k was constant that depended upon evapotranspiration/and M, was antecedant soil-moisture index. Input data were daily automatic rainfall records and daily automatic water level records from January 1996 to March 2000 which was taken from Ngunut I watershed. The watershed located in the upper Solo watershed area, Central Java, Indonesia. In this research, Hamon model was applied for three conditions: MHST to predict direct runoff for the whole year, MHMP for the wet season and MHMK for dry season. The result of this research were: for MHST, parameter c = 1.19189, k = 2.34815, a = 0.27339, b = 0.0184, M, = 5.11